Neuronal Nitric Oxide Mediates the Anti-Inflammatory Effects of Intestinal Ischemic Preconditioning - Varga Sándor (JOURNAL OF SURGICAL RESEARCH, 2019)
Ischemic preconditioning (IPC) can provide a defense against ischemia-reperfusion (IR)-induced acute inflammation and barrier dysfunction in many organs. Because nitric oxide (NO) has been implicated as a trigger or mediator in the IPC mechanism and because neuronal NO synthase (nNOS) is a dominant isoform of NOS in the gastrointestinal tract, our aim was to investigate the role of nNOS in IPC-induced protection after mesenteric IR.Intestinal IR was induced in sodium pentobarbital-anesthetized dogs by clamping the superior mesenteric artery for 60 min followed by 2 h of reperfusion (IR group; n = 7). In further groups, IPC was used (three cycles of 5-min ischemia/5-min reperfusion periods) before IR in the presence or absence of selective inhibition of nNOS with 7-nitroindazole (5 mg/kg, intravenously, in a bolus 15 min before IPC, n = 6 each). Changes in mesenteric vascular resistance, intramucosal pH (pHi), and small bowel motility were monitored. Plasma nitrite/nitrate levels, intestinal NO synthase activity, leukocyte accumulation, mast cell degranulation, and histologic injury were also determined.Ischemia significantly decreased mesenteric vascular resistance and pHi, whereas IR induced a temporary bowel hypermotility and acute inflammatory reaction. IPC facilitated pHi recovery, attenuated motility dysfunction, elevated NOS-dependent NO production, and reduced leukocyte accumulation, mast cell degranulation, and mucosal injury. Pretreatment with 7-nitroindazole halted the IPC-induced increase in NO availability, pHi recovery, and the anti-inflammatory and morphologic effects.Our data demonstrate that NO generated by intestinal nNOS plays a pivotal role in IPC-linked tissue protection by inhibiting an IR-related acute inflammatory response.